Well log analysis for lithology and fluid contacts in Rovuma Basin – Mozambique: Application of cluster and discriminant analyses. (January 2022) - Medja Ussalu, Jone Lucas; Bassrei, Amin
Abstract: This study applies the cluster and discriminant analyses in geophysical well log data from the Rovuma sedimentary Basin - Mozambique. The main objective was to determine the lithological profile and fluid contacts in reservoirs. Well log data from five wells drilled on the same basin were used. For the discrimination, a reference well was chosen for training, and the obtained functions from it were then applied to the remaining wells. The classification process comprehended three main phases, namely, the separation of shale/non-shale layers along the entire logged section, separation of water/hydrocarbon within reservoirs and the separation of oil/gas within hydrocarbon bearing zones. The two methods, cluster analysis and discriminant analysis, were applied in parallel and the results are compared in each classification phase. The quality of reservoirs was also assessed by applying cutoffs in relation to shale content and effective porosity, delineating net reservoirs. In general, both methods converged to the same lithological model and fluidtypes in reservoirs. Gas has been indicated as the most predominant hydrocarbon in the basin. Highlights: Cluster and discriminant analyses for lithology and fluidtype assessment. High potential for hydrocarbon production in the Rovuma Basin. Gas has been indicated as the most predominant hydrocarbon in the Rovuma Basin. It is more likely that the water from deep reservoirs in the Rovuma Basin is fresh.